Colostomy and quality of life after spinal cord injury: systematic review. Issue 6 (27th August 2020) - Waddell, O.; McCombie, A.; Frizelle, F.
Abstract : Background: Spinal cord injury (SCI) has a significant impact on the quality of life (QoL) of affected patients. The aim of this review was to determine whether colostomy formation improves QoL in patients with SCI. Methods: The Cochrane Register, MEDLINE, Embase and CINAHL were searched using medical subject headings. The search was extended to the reference lists of identified studies, ClinicalTrials.gov and the WHO International Clinical Trials Registry. All clinical trials that included spinal injury and QoL, time spent on bowel care, and patient satisfaction with stoma were assessed. Results: A total of 15 studies were found (including 488 patients with a stoma), of which 13 were retrospective cross‐sectional studies and two were case–control studies, one of which was prospective research. Nine of 11 studies focusing on QoL reported that patients' QoL was improved by the stoma, whereas the remaining two studies found no difference. Time spent on bowel care was significantly reduced in all 13 studies that considered this outcome, with patients reducing the average time spent on bowel care from more than 1 h to less than 15 min per day. All 12 studies assessing patient satisfaction with their stoma reported high patient satisfaction. Conclusion: Stoma formation improves QoL, reduces time spent on bowel care, and increases independence. Stoma is an option that could be discussed and offered to patients with spinal cord injury. Abstract : In this systematic review to determine whether colostomy formation improved the quality of life (QoL) in patients with spinal cord injury, outcomes assessed were QoL, time spent on bowel care, and patient satisfaction with the stoma. A total of 15 studies were included; colostomy formation improved QoL and time spent on bowel care, and more than 90 per cent of patients were satisfied with having a stoma. Stoma and spinal cord injury Abstract : Antecedentes: La lesión de la médula espinal ( Spinal Cord Injury, SCI) tiene una clara repercusión en la calidad de vida ( Quality of Life, QoL) de los pacientes que la sufren. El objetivo de este manuscrito fue determinar si la realización de una colostomía mejora la calidad de vida en pacientes con SCI. Métodos: Se realizó una búsqueda en los registros Cochrane, MEDLINE, Embase y CINAHL utilizando palabras clave. La búsqueda se extendió a la bibliografía de los estudios identificados, al clinictrials.gov y al Registro Internacional de Ensayos Clínicos de la OMS. Se evaluaron todos los ensayos clínicos que analizaron la lesión espinal y la calidad de vida, el tiempo dedicado al cuidado intestinal y la satisfacción del paciente con el estoma. Resultados: Se incluyeron 15 estudios (con 488 pacientes) de los que 13 fueron estudios transversales retrospectivos, 2 eran estudios caso‐control y uno era un estudio prospectivo. Nueve de los 11 estudios que analizaron la calidad de vida revelaron que la colostomía mejoraba la calidad de vida de los pacientes, mientras que en los 2 restantes no se encontraron diferencias. El tiempo dedicado al cuidado intestinal se redujo significativamente en los 13 estudios. De promedio, los pacientes redujeron el tiempo dedicado al cuidado intestinal de más de una hora por día a menos de 15 minutos. Los 12 estudios que evaluaron la satisfacción del paciente con la colostomía constataron una alta satisfacción de los pacientes con sus estomas. Conclusión: La construcción de un estoma mejora la calidad de vida, reduce el tiempo dedicado al cuidado intestinal y aumenta la independencia. El estoma es una opción que podría discutirse y ser ofrecida a pacientes con lesión de la médula espinal.